Benigne paroxistic positional vertigo and relationship with low vitamin D (Research, Society and Development, 2023)
Introduction: Hypovitaminosis D is related to an increase in the otoconia degeneration marker, contributing to benign paroxysmal positional vertigo (BPPV). Objective: to show whether or not there is a relationship between BPPV and low vitamin D. Methodology: narrative type review, to delimit the search, combinations of descriptors were used: “Benign paroxysmal positional vertigo x vitamin D”, “Paroxysmal positional vertigo benign x hypovitaminosis D” and “benign paroxysmal positional vertigo x vitamin D replacement”, in the following databases: Scientific Electronic Library Online (SciELO), Google Scholar, ResearchGate and National Library of Medicine (PubMed). Results and discussion: BPPV is a disease that alters balance and is most often idiopathic, with advanced age, head trauma, disorders affecting the inner ear and female gender as other predisposing factors. Its relationship with vitamin D lies in the fact that this vitamin regulates calcium and phosphorus and therefore acts on otoconia. Conclusion: Although there is no consensus, many studies associate hypovitaminosis D with BPPV.